THE HISTORICAL BASIS FOR SUSTAINABLE MODERNIZATION OF MASS PANEL RESIDENTIAL CONSTRUCTION IN THE CONTEXT OF THE "15-MINUTE CITY" CONCEPT - Derkach С. (Bulletin of Lviv National Environmental University. Series «Architecture and Construction», 2024)
Mass residential development during the Soviet era followed the principle of micro-districts and neighborhoods. As a result, the concept of a short-distance city is not new. However, with the introduction of the Sustainable Development Agenda, this idea has gained a new name: the "15-minute city." Researchers are also exploring the concepts of 20-minute and 30-minute cities. The need to redesign urban areas based on this principle arises from the necessity for accessibility to essential infrastructure, such as educational and medical institutions, shops, and recreational areas. As cities have grown, the reliance on private transport has increased, leading to higher energy consumption and environmental harm due to the emissions of harmful substances into the air. The 15-minute city concept promotes accessibility to daily necessities, including workplaces, within a 15 to 30-minute walk or bicycle ride. Sustainable modernization, which involves upgrading residential buildings based on principles of sustainable development, is an integral part of urban planning. The revitalization of old residential buildings, along with their surrounding areas, can be viewed through the lens of sustainable modernization in the context of the 15-minute city. The aim of this research is to shed light on this theoretical concept. Descriptive and visual methods are employed to provide justification and insight into the historical foundations and existing architectural and planning solutions of residential neighborhoods that can implement this principle. This concept offers the potential for complex modernization projects of old panel residential buildings, not just in Ukraine but also in other post-Soviet countries. Given that these panel residential buildings were constructed en masse following similar principles and designs, they represent a significant portion of the housing stock in these countries. The architectural and spatial planning of residential neighborhoods from the Soviet period supports the revitalization of such districts in line with the 15-minute city concept.